Development of Differentiated Learning Tools with Mathematics Problem Solving Based on ESD to Improve Critical Thinking Skills of Junior High School Students - Dian Kurniati; Afni Nur Rosyidah; Randi Pratama Murtikusuma; Didik Sugeng Pambudi; Nurcholif Diah Sri Lestari; Sharifah Osman; Percy Sepeng (Department of Mathematics Education Program IPI Garut, 2026)
Rendahnya kemampuan berpikir kritis siswa SMP dan keterbatasan perangkat pembelajaran berbasis Education for Sustainable Development (ESD) menjadi latar belakang penelitian ini. Penelitian ini bertujuan mengembangkan perangkat pembelajaran matematika pada materi perbandingan (senilai, berbalik nilai, dan skala) untuk meningkatkan kemampuan berpikir kritis siswa. Menggunakan model pengembangan 4D (Define, Design, Develop, Disseminate), penelitian dilakukan terhadap 32 siswa kelas VII C SMP Negeri 12 Jember. Instrumen pengumpulan data meliputi lembar validasi, observasi keterlaksanaan, tes hasil belajar, dan angket respons siswa. Hasil penelitian menunjukkan perangkat pembelajaran memenuhi kriteria: Valid, dengan rerata 3,92; Praktis, dengan persentase respons siswa 87% dan keterlaksanaan 100%; serta Efektif, dengan peningkatan hasil belajar melalui skor N-Gain sebesar 87%. Simpulan penelitian ini menunjukkan bahwa perangkat pembelajaran berbasis ESD layak digunakan dan berpotensi menjadi alternatif untuk meningkatkan kemampuan berpikir kritis siswa. The low critical thinking skills among junior high school students and the lack of learning resources based on Education for Sustainable Development (ESD) underpin this research. This study aims to develop mathematics learning materials on the topic of ratios—covering direct proportions, inverse proportions, and scales—to enhance students' critical thinking skills. Employing the 4D development model (Define, Design, Develop, Disseminate), the study involved 32 seventh-grade students at SMP Negeri 12 Jember. Data collection instruments included validation sheets, observation forms for instructional implementation, learning achievement tests, and student response questionnaires. The results indicate that the developed materials meet the following criteria: Valid, with an average score of 3.92; Practical, evidenced by an 87% student response rate and 100% instructional implementation; and Effective, demonstrated by an N-Gain score of 87% in learning outcomes. In conclusion, the ESD-based learning materials are feasible for classroom use and serve as a viable alternative to improve students' critical thinking skills.